A Mediterranean Meal Plan Modulates Human Milk Composition in Women With Obesity. (7th June 2021) - Sims, Clark, Martinez, Audrey; Andres, Aline
Abstract: Objectives: Human milk (HM) is impacted by both maternal obesity and diet. HM from women with obesity has higher fat, leptin and insulin concentrations. Additionally, maternal dietary fat intake is associated with increased HM fat content. The objective of this study was to determine the impact of a Mediterranean meal plan on the composition of HM from women with obesity. Methods: In this pilot study, thirteen women with obesity (body mass index (BMI) ≥ 30 kg/m 2 ) enrolled at five months post-partum and followed a provided Mediterranean meal plan focused on reducing fat intake and increasing unsaturated fat and fiber intake for four weeks. Participants' diet was assessed using Nutrition Data System for Research. HM was collected at baseline and after the 4-week intervention and the concentrations of metabolites, hormones and cytokines were assayed. Wilcoxon signed-rank tests and analysis of variance were used to assess changes in participant diet and HM composition. Summary statistics are presented as mean ± standard deviation. Results: The participants' Healthy Eating Index Score, a measure of diet quality, significantly improved (38.3 ± 5.13 vs. 78.2 ± 6.75, p < 0.001) and total fat intake was significantly lower (99.6 ± 23.3 g vs. 66.9 ± 12.0 g/day, p < 0.001) after the intervention. Human milk leptin (694 ± 464 pg/ml vs. 437 ± 324 pg/ml, p = 0.007) and tumor necrosis factor α (0.515 ± 0.267 pg/ml vs. 0.310 ± 0.127 pg/ml, p = 0.010) concentrations were lower post intervention, whereas HM macronutrient composition was unchanged. The concentrations of several individual human milk oligosaccharides (HMO) and total HMOs (7720 ± 797 nmol/ml vs. 6986 ± 940 nmol/ml, p = 0.049), as well as HM tyrosine concentration (18.2 ± 6.16 nmol/ml vs. 14.5 ± 4.69 nmol/ml, p = 0.005) were significantly lower post intervention. Conclusions: The composition of HM from women with obesity can be modulated by short-term adherence to a Mediterranean meal pattern. These findings merit further studies that use longer interventions and examine the impact of any changes in HM composition on infant growth and development. Modifying HM composition via a dietary intervention may provide a novel strategy to promote child development and health. Funding Sources: USDA ARS #6026-51, 000-010-05S and #6026-51, 000-012-06S, NIH/NIDDK R01DK107516, Arkansas Children's Research Institute/Arkansas Biosciences Institute GR037121.